A conductive foam: Based on novel poly(styrene‐b‐butadiene‐co‐styrene‐b‐styrene) tri‐block copolymer filled by carbon black. Issue 11 (11th November 2014) - Zhang, Jihai; Zhou, Tao; Zhao, Jing; Yuan, Canyao; Xia, Liping; Sun, Ningfeng; Zhang, Weidong; Zhang, Aimin
ABSTRACT In this article, a conductive foam based on a novel styrene‐based thermoplastic elastomer called poly(styrene‐b‐butadiene‐co‐styrene‐b‐styrene) tri‐block copolymer S(BS)S was prepared and introduced. S(BS)S was particularly designed for chemical foaming with uniform fine cells, which overcame the shortcomings of traditional poly(styrene‐b‐butadiene‐b‐styrene) tri‐block copolymer (SBS). The preparation of conductive foams filled by the carbon black was studied. After the detail investigation of cross‐linking and foaming behaviors using moving die rheometer, the optimal foaming temperature was determined at 180°C with a complex accelerator for foaming agent. Scanning electron microscopy (SEM) images shown that the cell bubbles of conductive foam were around 30–50 µm. The conductivity of foams was tested using a megger and a semiconductor performance tester. SEM images also indicated that the conductivity of foams was mainly affected by the distribution of carbon black in the cell walls. The formation of the network of the carbon black aggregates had a contribution to perfect conductive paths. It also found that the conductivity of foams declined obviously with the foaming agent content increasing. The more foaming agent led to a sharp increasing of the number of cells (from 2.93 × 106 to 6.20 × 107 cells/cm3) and a rapid thinning of the cell walls (from 45.3 to 1.4 µm), resulting in an effective conductive path of the carbon black no forming. The conductive soft foams with the density of 0.48–0.09 g/cm3 and the volume resistivity of 3.1 × 103−2.5 × 105 Ω cm can be easily prepared in this study. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41644.